Effects of autologous adipose-derived regenerative stem cells administered at the time of anterior cruciate ligament reconstruction on knee function and graft healing. (30th August 2019) - Alentorn-Geli, Eduard; Seijas, Roberto; Martínez-De la Torre, Adrián; Cuscó, Xavier; Steinbacher, Gilbert; Álvarez-Díaz, Pedro; Barastegui, David; Navarro, Jordi; Serra-Renom, José Maria; Nishishinya, Betina; Català, Jordi; Laiz, Patricia; et al.
Purpose: To compare the healing and clinical outcomes of anterior cruciate ligament (ACL) reconstruction between patients with or without intraoperative administration of adipose-derived regenerative stem cells (ADRC). Methods: Between 2013 and 2014, the outcomes of 20 soccer players undergoing ACL reconstruction using bone–patellar tendon–bone autograft infiltrated with ADRC at the end of the procedure were compared to a historical, matched cohort of 19 soccer players undergoing the same procedure without ADRC. Outcomes were obtained at baseline, and 6 and 12 months postop for IKDC (International Knee Documentation Committee), Lysholm, and Lequesne, and at 2, 4, 6, and 12 months postop for VAS (visual analogue scale) for pain and graft maturation to evaluate the ligamentization process (magnetic resonance imaging (MRI)-based). Results: Both groups significantly improved the IKDC ( p < 0.001 in both groups), Lysholm ( p < 0.001 in both groups), Lequesne index ( p < 0.001 in both groups), VAS for pain ( p = 0.002 for the ADRC and p < 0.001 for the control group), and MRI scores ( p < 0.001 in both groups) in the 12 months postop compared to baseline scores. However, there were no significant differences in the improvement of the outcomes between groups across time ( p > 0.05). All patients returned to sports after surgery, but 8 (40%) patients in the ADRC and 13 (68.4%) patients in the control group had lower Tegner activity score at 12 months postop. Conclusions: Patients receiving ADRC at the time of ACL reconstruction significantly improved knee function and healing/maturation of the graft at 12 months. However, this improvement was not statistically significant compared to a control group undergoing ACL reconstruction alone.